Generative Artificial Intelligence For Digital Marketing: Insights and Antecedents - A Systematic Literature Review - Kumar, Pritam; Satanasavapak, Punnaluck; Chantokul, Donyawan; Wang, Yunmei (Journal of Roi Kaensarn Academi, 2024)
The rapid rate of technological advancement is largely responsible for the enormous and far-reaching developments that have occurred in the field of digital marketing in just over a decade. Since the introduction of AI, businesses have seen significant changes to how they interact with customers, analyze data, and build marketing strategies. An emerging field in AI research, generative AI seeks to address challenges by generating new concepts, designs, and algorithms based on patterns that have already been learned. In light of the increasing demand for immediate, personalized interactions with customers, this systematic literature review aims to shed light on the present degree of generative AI deployment. A total of twenty publications were considered for this review based on the inclusion and exclusion criteria specified in the PRISMA guidelines. This research aims to take a look at digital marketing as it is now and how generative AI could improve things in terms of efficiency, creativity, and audience engagement. This research aims to bridge knowledge gaps on the impact of generative AI on digital marketing by examining existing techniques, new technology breakthroughs, and practical applications. Incorporating generative AI into marketing strategy gives businesses a chance to differentiate out by providing exceptional customer service.